Cognitive Rehabilitation Improves Functional Vision Skills in Children with Cerebral Visual Impairment - Zeynep Celik Turan; Esra Aki (Brain Sciences)
Background/Objectives: Cerebral visual impairment (CVI) is the leading cause of visual disability in children, resulting from damage to the brain’s visual processing pathways. Although ocular structures may be intact, functional vision, the use of vision in daily tasks, is often significantly affected. Cognitive Rehabilitation Therapy (CRT) has shown potential to enhance cognitive functions through neuroplasticity, yet its influence on functional vision remains underexplored. This exploratory pilot study aimed to examine whether CRT could improve functional vision in children with CVI by targeting underlying cognitive deficits. Methods: A single-arm pre–post intervention study was conducted with nine children aged 7–11 years diagnosed with CVI. Participants received 20 individualized CRT sessions over ten weeks, integrating principles from the Model of Visual Functioning. Functional vision was evaluated using the Gazi Functional Vision Assessment Instrument (GFVAI), while cognitive improvements were measured with the Dynamic Occupational Therapy Cognitive Assessment for Children (DOTCA-Ch) and the Motor-Free Visual Perception Test-4 (MVPT-4). Data were analyzed using Wilcoxon signed-rank tests. Results: Statistically significant improvements were observed in GFVAI domains such as light sensitivity, distant visual field, focusing, maintaining focus, and obstacle avoidance (p < 0.05 to p < 0.01). Qualitative analysis also indicated a shift from low/moderate to good/very good performance in most functional vision categories. Cognitive domains, including visual-motor organization, thinking operations, and spatial perception, showed significant gains. Conclusions: CRT may support improvements in functional vision by enhancing cognitive processes in children with CVI. This therapist-led approach is feasible, adaptable, and holds promise for widespread application in pediatric rehabilitation.